The bridge home - Venkatraman, Padma, 1969- (New York, NY : Nancy Paulsen Books, 2019)
Four determined homeless children make a life for themselves in Chennai, India.
Keywords: Homeless persons -- Fiction; Runaways -- Fiction; JUVENILE FICTION / Family / Siblings; JUVENILE FICTION / People & Places / Asia; JUVENILE FICTION / Social Issues / Runaways; Chennai (India) -- Fiction; India -- Fiction